Primary malignant melanoma of oral cavity: A report of three rare cases - Hanspal Singh; Priya Kumar; Jeyaseelan Augustine; Aadithya B Urs; Sunita Gupta (Wolters Kluwer Medknow Publications, 2016)
Oral malignant melanoma (OMM) is a rare tumor of melanocytic origin, accounting for 20-30% of malignant melanomas at the mucosal surface and 16% intra-orally. Hard palate and maxillary gingiva are the most common involved sites. In this case series, we present varying patterns of presentation of three cases of OMM with one case of distant metastasis. All cases in the current series presented at an advanced stage and died within a year of diagnosis. In conclusion, due to the aggressive clinical course and poor prognosis of this deadly lesion, it is of paramount importance to maintain a high index of suspicion for early detection and diagnosis for any pigmented lesion in the oral cavity.